Competing risks of death and kidney failure in a cohort of Australian adults with severe chronic kidney disease. Issue 3 (5th December 2021) - Jose, Matthew D; Raj, Rajesh; Jose, Kim; Kitsos, Alex; Saunder, Tim; McKercher, Charlotte; Radford, Jan
Abstract: Objectives: To examine the competing risks of death (any cause) and of kidney failure in a cohort of Australian adults with severe chronic kidney disease. Design: Population‐based cohort study; analysis of linked data from the Tasmanian Chronic Kidney Disease study (CKD.TASlink), 1 January 2004 – 31 December 2017. Participants: All adults in Tasmania with incident stage 4 chronic kidney disease (estimated glomerular filtration rate [eGFR], 15‒29 mL/min/1.73 m 2 ). Main outcome measures: Death or kidney failure (defined as eGFR below 10 mL/min/1.73 m 2 or initiation of dialysis or kidney transplantation) within five years of diagnosis of stage 4 chronic kidney disease. Results: We included data for 6825 adults with incident stage 4 chronic kidney disease (mean age, 79.3 years; SD, 11.1 years), including 3816 women (55.9%). The risk of death increased with age — under 65 years: 0.18 (95% CI, 0.15–0.22); 65‒74 years: 0.39 (95% CI, 0.36‒0.42); 75‒84 years, 0.56 (95% CI, 0.54‒0.58); 85 years or older: 0.78 (95% CI, 0.77‒0.80) — while that of kidney failure declined — under 65 years: 0.39 (95% CI, 0.35–0.43); 65‒74 years: 0.12 (95% CI, 0.10‒0.14); 75‒84 years: 0.05 (95% CI, 0.04‒0.06); 85 years or older: 0.01 (95% CI, 0.01‒0.02). The risk of kidney failure was greater for people with macroalbuminuria and those whose albumin status had not recently been assessed. The risks of kidney failure and death were greater for men than women in all age groups (except similar risks of death for men and women under 65 years of age). Conclusions: For older Australians with incident stage 4 chronic kidney disease, the risk of death is higher than that of kidney failure, and the latter risk declines with age. Clinical guidelines should recognise these competing risks and include recommendations about holistic supportive care, not just on preparation for dialysis or transplantation.